Glosses of the Peresopnytsia Gospel in the Context of Styles Interaction (Linguostylistic Studies, 2017)
The article considers the glosses in the text of the Peresopnytsia Gospel as an evidence of the interaction of the colloquial and bookish elements in the Ukrainian writing language of the 16-th century. The emphasis is laid on the considerable penetration of the Ukrainian lexicon into the translated literature, the formation of a new lexical norm. Author reveals numerous Ukrainian lexical equivalents to the Greek, Old Hebrew, Old Slavonic, Common Slavonic and Latin lexical units. Widespread use of synonymous specific Ukrainian words along with foreign words may be attributed to the fact that in the Old Ukrainian language of the 10-th century there were enough lexical means to express/convey the concepts in the texts of the confessional style. It has been revealed that glosses to foreign nominations were cited purposefully to replace the words of the source language origin with the Ukrainian lexical equivalents. The key findings of the study confirm the hypothesis that the wide penetration of the folk/spoken vocabulary into the translated Gospel text was the major factor that influenced the formation of the Ukrainian confessional style.
Keywords: glosses; glosseme; Peresopnytsia Gospel; translation; lexical equivalents; synonyms